Microbiome and Cognitive Impairment: Can Any Diets Influence Learning Processes in a Positive Way? - Novotný, Michal; Klimova, Blanka; Valis, Martin (Frontiers in Aging Neuroscience, 2019)
The aim of this review is to summarize the effect of human intestinal microbiome on cognitive impairments and to focus primarily on the impact of diet and eating habits on learning processes. Better understanding of the microbiome could revolutionize the possibilities of therapy for many diseases. The authors performed a literature review of available studies on the research topic describing influence of human microbiome and diet on cognitive impairment or learning processes found in the world’s acknowledged databases Web of Science, PubMed, Springer, and Scopus. The digestive tube is populated by billions of living microorganisms including viruses, bacteria, protozoa, helminths, and microscopic fungi. In adulthood, under physiological conditions, the intestinal microbiome appears to be relatively steady. However, it is not true that it would not be influenced, both in the positive sense of the word and in the negative one. The basic pillars that maintain a steady microbiome are genetics, lifestyle, diet and eating habits, geography, and age. It is reported that the gastrointestinal tract and the brain communicate with each other through several pathways and one can speak about gut-brain axis. New evidence is published every year about the association of intestinal dysbiosis and neurological/psychiatric diseases. On the other hand, specific diets and eating habits can have positive effect on a balanced microbiota composition and thus contribute to the enhancement of cognitive functions, which are important for any learning process.